Geomorphological, Electrical Resistivity and Magnetic Methods for Assessing Groundwater Potential in Adet Town, West Gojam, Ethiopia - Belay Sitotaw Goshu; Kirubel Molla (Britain International for Academic Research (BIAR) Publisher, 2026)
Imagine the sun-scorched fields of Adet Town, West Gojam, and Ethiopia, where families rise each day with a flicker of hope, their hands calloused from carrying water across cracked earth. This study,